Is Eminectomy Effective in the Management of Chronic Closed Lock? - Stassen, Leo (My University, 2020)
Purpose: This study assesses the effectiveness of eminectomy in the management of chronic closed lock, refractory to conservative medical management in the largest multicentred study of its kind in the UK, with a cohort of 167 patients. Temporomandibular mandibular joint disorder affects 30% of adults in the UK. Chronic closed lock is a well-documented sub-type. Method: A retrospective study of patients with refractory closed lock was carried out, where conservative management had been implemented for a minimum of 6 months. Refractory patients were offered eminectomy at three separate centres over a period from 1995 to 2011. The primary variable was the inter-incisal distance (IID). Other variables included pain, clicking and nerve damage preand post-operatively. Results: There were 167 patients across all three centres, 81% of which were female. The mean IID was 23 mm preoperatively and 37 mm post-operatively. There was a statistically significant association with the primary predictor variable, yielding a p value of \ 0.05. Clicking resolved completely post-operatively in 84 patients (58%). Pain subjectively improved in 56% cases. Conclusion: Eminectomy is a safe and effective surgical procedure and has a role to play as a second-line surgicaloption in the management of closed lock after more conservative medical options have failed. Conclusion Eminectomy is a safe and effective surgical procedure and has a role to play as a second-line surgical
PUBLISHED
Keywords: Temporomandibular joint; Temporomandibular joint dysfunction; Closed lock; Eminectomy